2013
DOI: 10.1098/rspb.2012.2963
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic history of gene duplications and losses characterizes the evolution of the SPARC family in eumetazoans

Abstract: The vertebrates share the ability to produce a skeleton made of mineralized extracellular matrix. However, our understanding of the molecular changes that accompanied their emergence remains scarce. Here, we describe the evolutionary history of the SPARC (secreted protein acidic and rich in cysteine) family, because its vertebrate orthologues are expressed in cartilage, bones and teeth where they have been proposed to bind calcium and act as extracellular collagen chaperones, and because further duplications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 62 publications
(86 reference statements)
2
33
0
Order By: Relevance
“…Therefore, the comparative analysis of turbot Sparc primary sequence with other SPARC proteins from diverse vertebrate species and specifically with its teleost orthologs suggests a strong evolutionary conservation pressure for this protein and also indicates that conservation in function should exist. Although, we did not find any other sparc paralogous in turbot, we have to mention the possibility that turbot genoma might contain two additional sparc paralogues, sparcl1 and sparcb as discovered in other teleost like zebrafish or trout (Bertrand et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, the comparative analysis of turbot Sparc primary sequence with other SPARC proteins from diverse vertebrate species and specifically with its teleost orthologs suggests a strong evolutionary conservation pressure for this protein and also indicates that conservation in function should exist. Although, we did not find any other sparc paralogous in turbot, we have to mention the possibility that turbot genoma might contain two additional sparc paralogues, sparcl1 and sparcb as discovered in other teleost like zebrafish or trout (Bertrand et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, phylogenetic analysis indicated that SPARC/SPARCL1 has been roughly identified in both protostomes and deuterostomes, and a related gene (sparcb) has also been found in tunicates, amphioxus and zebrafish (Bertrand et al, 2013). In Turbot, Sparc clusters together with its vertebrate orthologues and teleost Sparcs were arranged into a single clade.…”
Section: Discussionmentioning
confidence: 97%
“…The classical evolutionary scenario posits that the SPARC-L1 and SPARC paralogues arose from two rounds of vertebrate-specific genome duplications [34, 35]. The gar and coelacanth SPARC-L1 genomic loci were recently shown to contain a SPARC-L2 gene of unknown evolutionary history [5, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Markers for a number of genes implicated in vertebrate chondrogenesis and osteogenesis including collagens FCol1 and FCol2, SPARC, soxE and runx were expressed specifically in the tips of the regenerating skeletal rods. Amphioxus in fact possesses two SPARC genes, conserved since the eumetazoan ancestor, both of which are expressed in the notochord during embryonic development (Bertrand et al, 2013). Combined with expression data in other chordates, this leads the authors to suggest that co-expression of SPARC-like and Collagen proteins in mesenchymal cells was one of the key steps to skeletal evolution (Bertrand et al, 2013).…”
Section: Cirrus Regenerationmentioning
confidence: 88%
“…Amphioxus in fact possesses two SPARC genes, conserved since the eumetazoan ancestor, both of which are expressed in the notochord during embryonic development (Bertrand et al, 2013). Combined with expression data in other chordates, this leads the authors to suggest that co-expression of SPARC-like and Collagen proteins in mesenchymal cells was one of the key steps to skeletal evolution (Bertrand et al, 2013). Indeed, a SPARC gene and runx2 are expressed in prospective scleroblast progenitors during scale regeneration in the goldfish, a collagenous dermal skeleton component (Iimura et al, 2012).…”
Section: Cirrus Regenerationmentioning
confidence: 99%